ANTAGONISM OF ISOLATES OF Trichoderma spp. at EGARD OF Botrytis cinerea Pers. AGENT OF GRAY ROT OF TOMATO (Lycopersicum esculentum Mill.) UNDER GREENHOUSE - D., Saddek1,2*, Bendifallah4 L., Bencheikh2 K. (university of eloued جامعة الوادي, 2020)
The study of the antagonistic activity of eleven isolates of Trichoderma spp., against four isolates of Botrytis cinerea, collected from diseased tomato plants cultivated in greenhouses located on the Algiers coast and in the north-east of Sahara. The in vitro antagonism was compared to the fungicidal activity of "PROLEX", widely used by farmers against this phytopathogen in Algeria. The results revealed a complete inhibition of sporulation, germination, production and germination of sclerotia as well as morphological changes in vitro. A significant reduction on their pathogenicity and a strong inhibition of their sporulation were recorded in vivo. In conclusion, the Trichoderma spp. antagonists in particular, the "T4, T11, T8 and T10" isolates are therefore promising for the biocontrol of grey mould of tomato.
artical
Keywords: Trichoderma spp; Botrytis cinerea; activité antagoniste; Lycopersicum esculentum Mill; Prolex.